Performance Evaluation of a Real Vehicular Delay-Tolerant Network Testbed. (22nd March 2015) - Paula, Maicke C. G.; Rodrigues, Joel J. P. C.; Dias, João A.; Isento, João N.; Vinel, Alexey
Vehicular Delay-Tolerant Networks (VDTNs) are a breakthrough based DTN solution used to provide vehicular communications under challenging scenarios, characterized by long delays and sporadic connections. Using the store-carry-and-forward paradigm, this technology allows in-transit bundles to asynchronously reach the destination hop by hop over traveling vehicles equipped with short-range wireless devices. The VDTN architecture assumes out-of-band signaling with control and data planes separation and follows an IP over VDTN approach. This paper presents a real-world VDTN prototype evaluated through a safety application and a Traffic Jam Information Service. It also demonstrates the real deployment of this new vehicular communication approach. The real testbed is an important contribution since some complex issues presented in vehicular communication systems can be studied more accurately in real-world environments than in a laboratory approach. The results confirm that real deployment of VDTNs is doable and can be seen as a very promising technology for vehicular communications, although it requires appropriated technologies for outline interferences and quality of service support.